KEBIJAKAN AKUNTANSI LINGKUNGAN UNTUK MENDUKUNG PARIWISATA BERKELANJUTAN DI KAWASAN DANAU TOBA PROVINSI SUMATERA UTARA - Azizul Kholis (Inovasi, 2022)
This study aims to analyze environmental accounting policies implemented by companies in the area around Lake Toba, North Sumatra province. Based on the theory and sustainability which includes three aspects, namely economic, environmental and social, these three factors in this study determine the company's environmental accounting policies. The economic proxy is measured through the company's management support, the environmental proxy is the CSR policy and the social proxy is the role. Sampling was carried out on 73 companies in Simalungun, Toba, Samosir, Dairi, Humbang Hasundutan, North Tapanuli, and Karo Regencies. The analysis technique used is multiple regression with the results of the study showing that CSR Policy (X1), Management Support (X2) and Community Support (X3), have a significant influence on the company's environmental accounting policy (Y). The limitation of this research is that the sample does not group companies by business category, so that environmental accounting policies may differ from one company to another. The novelty and innovation of this research is related to the company's environmental policy which is estimated to have a contribution to sustainable sustainability. The recommendation for further research is to be able to select research samples in one group of similar business categories, for example in the hotel business, travel or air transportation services. The results of the study also prove that awareness of sustainable tourism is met by the company's management as evidenced by the existence of a CSR support program in the Lake Toba area. Keywords: Accounting, Environment, Touristm, Sustainability